Impact of dietary patterns on the survival outcomes of patients with cardiovascular disease - Sun, Jinyu; Jiang, Xingyu; Li, Zheng; Shen, Yang (Frontiers in Nutrition, 2025)
BackgroundThis study examines the association between dietary patterns and survival outcomes in patients with cardiovascular disease (CVD).MethodsA total of 9,101 adults with CVD from the 2005–2018 National Health and Nutrition Examination Survey were included. Dietary patterns were evaluated using five indices: the Alternative Healthy Eating Index (AHEI), Dietary Approaches to Stop Hypertension (DASH), Dietary Inflammatory Index (DII), Healthy Eating Index-2020 (HEI-2020), and the Alternative Mediterranean Diet Score (aMED). Associations between dietary indices and all-cause mortality were assessed using Kaplan-Meier survival analysis, weighted Cox regression models, and restricted cubic spline analyses. Predictive performance was evaluated using time-dependent receiver operating characteristic (Time-ROC) curves.ResultsAfter a median follow-up of 7 years, 1,225 deaths were recorded. Survivors had higher AHEI, DASH scores, and lower DII scores. Kaplan-Meier analysis suggested better survival outcomes associated with higher adherence to healthier dietary patterns (AHEI, DASH, HEI-2020, aMED) and lower adherence to pro-inflammatory diets (DII). Weighted Cox regression revealed significant associations between higher scores on AHEI, DASH, HEI-2020, and aMED and reduced mortality risk (highest vs. lowest tertile HRs: 0.59, 0.73, 0.65, and 0.75, respectively; all P < 0.05). Conversely, higher DII scores were associated with increased mortality risk, with the highest tertile showing significantly elevated risk compared to the lowest tertile (HR = 1.58, 95% CI: 1.21–2.06; P < 0.001). Restricted cubic spline analyses identified a significant non-linear relationship between AHEI scores and mortality (P fornon–linearity = 0.036), while other indices exhibited linear associations. Time-ROC analysis indicated that dietary indices maintain relatively consistent predictive effectiveness for mortality risk over time.ConclusionImproved healthy dietary patterns could potentially reduce mortality risk in CVD patients, underscoring the need for dietary quality enhancement in managing CVD.